2013
DOI: 10.1371/journal.pone.0076219
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Neutrophilic Migration Revealed by the Crystal Structure of the Chemokine Receptor CXCR2 in Complex with the First PDZ Domain of NHERF1

Abstract: Neutrophil plays an essential role in host defense against infection, but uncontrolled neutrophilic infiltration can cause inflammation and severe epithelial damage. We recently showed that CXCR2 formed a signaling complex with NHERF1 and PLC-2, and that the formation of this complex was required for intracellular calcium mobilization and neutrophilic transepithelial migration. To uncover the structural basis of the complex formation, we report here the crystal structure of the NHERF1 PDZ1 domain in complex wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 46 publications
6
30
0
Order By: Relevance
“…We have recently shown that the NHERF1-scaffolded CXCR2-PLC-β complexes regulate CXCR2 signaling in neutrophils and pancreatic cancer cells (Wu et al, 2012;Wang et al, 2013). We also demonstrated the direct interaction between NHERF1 and CXCR2 as well as NHERF1 and PLC-β3 in the crystal structure studies (Lu et al, 2013;Jiang et al, 2013Jiang et al, , 2014. It is therefore conceivable that CXCR2 could also mediate potential interaction with certain PDZ scaffold proteins in EPCs.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…We have recently shown that the NHERF1-scaffolded CXCR2-PLC-β complexes regulate CXCR2 signaling in neutrophils and pancreatic cancer cells (Wu et al, 2012;Wang et al, 2013). We also demonstrated the direct interaction between NHERF1 and CXCR2 as well as NHERF1 and PLC-β3 in the crystal structure studies (Lu et al, 2013;Jiang et al, 2013Jiang et al, , 2014. It is therefore conceivable that CXCR2 could also mediate potential interaction with certain PDZ scaffold proteins in EPCs.…”
Section: Discussionmentioning
confidence: 54%
“…We showed that CXCR2 and its downstream signaling molecule PLC-β are clustered by a PDZ adaptor protein NHERF1 which scaffolds a CXCR2-PLC-β complex through PDZ-mediated interactions (Wu et al, 2012;Wang et al, 2013). We also reported the crystal structure of the complex formation by X-ray crystallization, which provides the structural basis for CXCR2-mediated cellular functions in neutrophils and pancreatic cancer cells (Lu et al, 2013;Jiang et al, 2014). However, the putative role and the molecular mechanisms that underlie the functional significance of potential PDZ-based CXCR2 complexes in EPC mobilization, homing, and incorporation into neovasculature have not been determined.…”
Section: Introductionmentioning
confidence: 88%
“…The overall structure of PDZ-RhoGEF PDZ is similar to other PDZ domains [5], consisting of six β strands (β1–β6) and two α-helices (αA and αB) (Fig. 1B).…”
Section: Resultsmentioning
confidence: 71%
“…However, swift signaling requires direct and indirect interaction of CXCR2 with other membrane receptors, channels, intracellular scaffold proteins, effectors, and cytoskeletal elements, among which PDZ domain-containing proteins play a central role in efficient signaling by scaffolding the formation of macromolecular complexes at the plasma membrane and functionally coupling chemokine signaling to downstream signaling events [1]. In general, PDZ domains mediate protein interaction by recognizing the C-terminal sequence of target proteins and binding to the targets through a canonically and structurally conserved PDZ peptide-binding pocket [5]. The specificity of the interaction is determined mainly by the residues at positions 0 and −2 of the peptides (position 0 referring to the C-terminal residue), whereas other residues do not significantly contribute to the interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Note that residues His26 and Arg37 shared by the ligand binding site and the SCN binding site are highly conserved (Fig. 1D), and these sites have been implicated in ligand-specific interactions in other PDZ domains [30,31]. Therefore, strategies aiming at exploiting the novel SCN binding site may represent a promising approach to achieve NHERF2-inhibitor selectivity that would allow the differentiation among a wide range of NHERF2-mediated interactions.…”
Section: Resultsmentioning
confidence: 99%